Urgensi Dalam Pelaksanaan Pencatatan Nikah Perpektif Hukum Positif di Indonesia - Khomsutamam; Andaryuni, Lilik (Bulletin of Community Engagement, 2024)
Marriage is an important aspect of human life that requires legal regulation to maintain the continuity of the family. Marriage registration in Indonesia has an urgency in ensuring the validity and legal protection of married couples. This research uses a descriptive analysis approach to examine the rules for registering marriages in the 1974 Marriage Law and the Compilation of Islamic Law. Data was obtained through literature study and analysis of related regulations. From this research, it was found that marriage registration has an important role in maintaining the validity of marriages and providing legal protection for couples. An effective registration process can facilitate the implementation of the 1974 Marriage Law. Based on the research results, it is recommended to increase socialization regarding the importance of marriage registration in society. The government also needs to pay attention to the implementation of regulations regarding marriage registration to strengthen legal protection for married couples in Indonesia. Marriage registration has a vital role in maintaining the validity of marriages and providing legal protection for couples. Further efforts are needed to improve understanding and implementation of relevant regulations to strengthen the institution of marriage in Indonesia.